The Effect of Domain Deformation on the Behavior of a Distributed Kinetic System - E. P. Kubyshkin (Моделирование и анализ информационных систем, 2013)
The behavior of a distributed kinetic system, which is in homogeneous equilibrium within a flat circular reactor, under circular domain deformation is studied. We show that the deformation of domain may lead to appearance of stable spatially inhomogeneous oscillatory solutions, including chaotic oscillations (strange attractors), in the neighborhood of homogeneous equilibrium. We also speak about mechanisms of initiation of chaotic attractors and calculate Lyapunov exponents and Lyapunov dimension for these regimes. We call this mechanism of appearance of spatially inhomogeneous nonlinear oscillations in distributed kinetic system the domain effect.